Strategies for the management of human talent in the associations of yuqueros attached to Colfeyuca in Sucre, Colombia - Cardona-Arbeláez, Diego; Alzate-Alvarán, Julieth Cecilia; Lora-Guzmán, Harold (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this article is to identify strategies for the management of human talent that are currently being developed by the yuqueras associations of the department of Sucre, Colombia. The analysis is carried out in light of the theory of corporate social responsibility, based on the indicators of the Ethos Institute in Brazil. The research has a qualitative approach, in which in-depth interviews were conducted with the leaders of ten associations of cassava growers; Likewise, the observation was an important part of the study, which complemented the analysis of the information. The results indicate that the associations, in spite of being constituted legally, do not advance actions in favor of the management of human talent, and this is basically due to ignorance on the subject. However, there is an intention to change, because associations recognize the importance of human talent within companies. This has led them to join and manage training and resources jointly, to promote union growth.